NEIGHBORS’ RIGHTS AND ABUSE OF RIGHTS - Lazic, Miroslav R (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
This paper deals with the analysis of property and its limitations in neighbour-law relationships, as well as the restrictions of property and neighbours rights due to the prohibition of abuse of rights thereof. Neighbours rights set boundaries in the content of the right to property, whereas the prohibition of abuse of rights additionally set restrictions to the freedom of exercising such recognised content of rights. The purpose of this paper is to point out to the basic differences between neighbourhood rights and the prohibition of abuse of rights, but also to an occasional intertwinement of their effects and functions.
Keywords: ownership; neighbours’ rights; abuse of rights